Can DNA barcoding be used to identify closely related Clunio Haliday, 1855 species (Diptera: Chironomidae, Orthocladiinae)? - Michalova, Paraskeva; Lencioni, Valeria; Nenov, Momchil; Nikolov, Svetoslav (Zootaxa, 2021)
DNA barcoding based on a fragment of mitochondrial Cytochrome C Oxidase subunit 1 gene (COI) was applied to the two chironomids Clunio balticus Heimbach (690 base pairs) and C. ponticus Michailova (691 base pairs). The two species differed by one deletion in the nucleotide sequence Adenine. However, the 658-nucleotide long sequences of DNA from the mitochondrial Cytochrome C Oxidase subunit 1 gene (COI) of C. balticus and C. ponticus were identical upon comparison. Further, they compared with homologous sequences for C. marinus Holiday and C. tsushimensis Tokunaga from the Barcode of Life (BOLD) database and the results plotted as a weighted graph, where C. tsushimensis, C. marinus and C. balticus C. ponticus formed three almost equidistant groups. From this, we established that the genetic distance between the respective COI sequences of C. balticus and C. ponticus is minimal, indicating a close relationship between the species indicative of recent common origin. However, the comparative analysis between C. tsushimensis, C. marinus, C. balticus and C. ponticus showed a wider divergence in their respective nucleotide sequences. Overall, our results emphasized that the COI region does not work well as a DNA barcode to identify species within the Clunio genus. Either longer sequences or a multifaceted methodological approach, including morphology, cytogenetic and ecology is needed to distinguish some members of Clunio genus.